Analysis Of The Factors That Influence Islamic Bank Capital Buffers In Indonesia - Hisan, Ulis fajar Choirotun; Septiarini, Dina Fitrisia; Filianti, Dian (AKRUAL: Jurnal Akuntansi, 2020)
Banks are trust institutions. An appropriate tool in sustaining trust is the capital adequacy of the bank (capital buffer). This study aims to analyze the effect of financing risk (NPF), operational risk (BOPO), market risk (NI), Third Party Funds (DPK), GDP Growth (GDPG) and inflation on BUS capital buffers in Indonesia during the 2014-2018 period. This study uses panel data regression method with a sample of 12 BUS based on purposive sampling technique. BOPO, DPK, GDPG, and INF were found to have a significant effect on BUFF, where BOPO, DPK, and INF had a negative effect, while GDPG was positive. So operational risk, third party funds, GDP Growth, and inflation can be said to be determinants of BUS capital buffers in Indonesia in the 2014-2018 period. Financing risk (NPF) and market risk (NI) have no significant effect on BUS capital buffer in the study period. Regarding basel III implementation, operational risk is a significant determinant of capital buffer, and capital buffer is found to be procyclical to the Indonesian economy. Future studies can include more risk measurement variables and other macroeconomic variable